WANTAH GEOMETRI, SIMETRI, DAN RELIGIUSITAS PADA RUMAH TINGGAL TRADISIONAL DI INDONESIA - Agusinta Dewi, Ni Ketut (Jurnal Natah; Vol. 1, No. 1 Februari 2003, 2012)
Phenomenon of traditional housing in Indonesia is a culture expression of local community, not only its have relation with their building physics, but also the spirit and soul. Housing phenomenon by vernacular community of Indonesia which have mean to be a space to built their religion. As their perception to nature, they build housing base on geometry forms to perceive the appreciation of nature and the Creator. Orientation is required by man as a himself orientation, and symmetrical means a basic human balance as their solemnity for God. This paper describes religious phenomenon of vernacular community in Indonesia in to geometry and symmetrical forms that they being their identity expression of housing.
Keywords: symmetrical, geometry, religiuos, solemnity, traditional housing.